Common Mechanism of Pathogenesis in Gastrointestinal Diseases Implied by Consistent Efficacy of Single Chinese Medicine Formula. Issue 27 (July 2015) - Ling, Wei; Li, Yang; Jiang, Wei; Sui, Yi; Zhao, Hai-Lu; Kantarceken., Bulent
<x xml:space="preserve">Abstract</x> Abstract Gastrointestinal (GI) disorders often manifest similar symptoms with overlapping clinical diagnosis and unmet medical needs. Traditional Chinese medicine (TCM) has history-proven benefits for GI diseases; albeit language barrier prevents Western readers from accessing the original reports in Chinese. The TCM formula Si-Ni-San (SNS) consists of 4 herbs targeting on homeostatic disturbances characterized by "reflux" and "irritable" problems. Here we used SNS as a therapeutic tool to explore the common mechanisms of pathogenesis in non-neoplastic GI diseases. Data sources from PUBMED, Chinese National Knowledge Infrastructure, and Wanfang databases were searched for clinical trials. Comparisons were SNS as intervention and Western conventional medicine as control, which treat patients with upper GI disorders (gastroesophageal reflux disease, peptic ulcer, chronic gastritis, duodenogastric reflux), lower GI diseases (irritable bowel syndrome, ulcerative colitis), and functional dyspepsia. Participants and studies in accordance with the Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement were eligible. We used the Jadad scale to assess methodological qualities, the fixed or random-effect model to evaluate therapeutic efficacy, and the funnel plots to explore publication bias. Outcome was clinical efficacy defined by symptom relief with normal GI endoscopy, radiology, and pathology. We included 83 studies involving 7762 participants: 1708 versus 1397 of the upper GI disorders in 34 studies, 901 versus 768 of the lower GI diseases in 19 studies, 1641 versus 1348 of functional dyspepsia in 30 studies, and 328 versus 287 of relapse rate in 8 studies. Six studies had a Jadad score >2 points and the rest were <2 points. Pooled data showed significant efficacy of SNS for the upper GI disorders (odds ratio [OR] = 3.9, 95% confidence interval [CI] = 3.09–4.92), lower GI diseases (OR = 4.91, 95% CI = 3.71–6.51), and functional dyspepsia (N = 2989; OR = 3.94, 95% CI = 3.17–4.90). The relapse rate was 12.9% for SNS, significantly <46.5% for conventional therapies (OR = 0.16, 95% CI = 0.11–0.25). The consistent efficacy of the single TCM formula implicates common mechanisms of pathogenesis in GI disorders.